Cost Analysis of Water Purification Methods in India - Anand M. Sharan; Sarita Sharan (The Global Environmental Engineers, 2015)
In this work, cost analysis of commonly used RO method, Ultra-Violet method and the new Pressure Cooker method is performed. These methods studied here relate to the production of potable water which meets the World Health Organization (WHO) standards. The advantages of the use of the Pressure Cooker method over the two other methods for undeveloped countries are explained. The results show that not only the Pressure Cooker method is most economical but also is very versatile as far as its use in rural India or other under-developed countries are concerned.